Malignant pheochromocytoma invading the ureteral wall muscle layer: A case report - Guang-Jie Li; Chao-Hong Zhang; Li-Xing Jiang; Hai-Qing Fan; Hui-Long Fang; Yu-Ye Wu (Urology Case Reports)
Pheochromocytoma is a neuroendocrine tumor for which surgical resection is the main treatment.Malignant pheochromocytoma is very rare. Here,we present a case of adrenal pheochromocytoma invading the ureteral wall muscle layer, which resulted in left adrenal and left nephrectomy.